Customer knowledge management improving customer relationship through knowledge application - Wilde, Silvio (Springer eBooks., 2011)
Managing and transferring knowledge - at the right time, in the right place and with the right quality for customers - enables companies to survive in times of fierce competition. The focus of this work is therefore on Knowledge Management and Customer Relationship Management. The theoretical part comprises several approaches to knowledge, its transfer and the barriers to be overcome when sharing knowledge. This is followed by a description of CRM and CKM (Customer Knowledge Management), outlining how crucial their successful use is. The practical part explores on the one hand the dependence on knowledge and on the other hand its availability for a good customer relationship. It includes a case study that investigates both the administrative and the operational area of a concrete company. The survey results are then discussed in detail, key success factors identified and mistakes pointed out. After this critical analysis, final recommendations are given that every company can benefit from.